Triphenylamines Induce Cell Death Upon 2-Photon Excitation - Rahima Chennoufi; Florence Mahuteau-Betzer; Patrick Tauc; Marie-Paule Teulade-Fichou; Eric Deprez (Molecular Imaging)
Photodynamic therapy (PDT) is a promising therapeutic method for several diseases, in particular for cancer. This approach uses a photosensitizer, oxygen, and an external light source to produce reactive oxygen species (ROS) at lethal doses to induce cell death. One drawback of current PDT is the use of visible light which has poor penetration in tissues. Such a limitation could be overcome by the use of novel organic compounds compatible with photoactivation under near-infrared light excitation. Triphenylamines (TPAs) are highly fluorescent compounds that are efficient to induce cell death upon visible light excitation (458 nm), but outside the biological spectral window. Interestingly, we recently showed that TPAs target cytoplasmic organelles of living cells, mainly mitochondria, and induce a high ROS production upon 2-photon excitation (in the 760-860 nm range), leading to a fast apoptosis process. However, we observed significant differences among the tested TPA compounds in terms of cell distribution and time courses of cell death–related events (apoptosis vs necrosis). In summary, TPAs represent serious candidates as photosensitizers that are compatible with 2-photon excitation to simultaneously trigger and imaging cell death although the relationship between their subcellular localization and the cell death mechanism involved is still a matter of debate.